Femtosecond Pulse Compression With Pedestal Suppression in a Sagnac Interferometer Constructed of Anti-Resonant Hollow Core Fiber - Taoying Yu; Xuesong Liu; Andrey Pryamikov; Alexey Kosolapov; Zhongwei Fan (IEEE Photonics Journal, 2021)
In this paper, compression of high-power femtosecond pulses in Sagnac interferometers constructed of anti-resonant hollow core fibers (ARHCF) is investigated numerically and experimentally. By varying the types and pressures of gas filled in the hollow core fiber, the group velocity dispersion and the nonlinear pulse phase accumulation difference between clockwise and counterclockwise propagations could be tuned conveniently. In experiment, we demonstrate the pedestal suppression temporal pulse compression of 800 nm, 160 fs, 10 μJ pulses from a Ti: Sapphire laser at 1 kHz to 20 fs with maximum compression efficiency of 25% nearly and compression ratio of eight.